Learning PMR history subject using multimedia. - A. Halim, Fatin Nudra Syafiqah; Zeki, Akram M. (IIUM Press, 2011)
Most students realize that they are not able to score History subject well due to there are many facts that they have to remember. They have no choice other than read the History text books to study and score in their exams. The problem arises when students are not really interested by reading text books so this will affect the performance of the students as well as schools. Mostly students do not interest to read text book to study this subject. This project is about a multimedia whereby it is provided an interactive multimedia that needs students to answer the questions that will be asked. This multimedia will be using by Form 1, Form 2 and Form 3 students in Malaysia.